Umroh Service Information System at El-Fajr Palembang - Lestari, Oktaviyani (PT. Lentera Ilmu Publisher, 2024)
This article explores the integration of web technology in managing prospective Umrah pilgrims at El-Fajr Tour and Travel Palembang. In response to the rapid evolution of communication technology, the study emphasizes the efficiency and effectiveness of web-based communication in connecting users across diverse locations. El-Fajr Palembang, founded in 2018, envisions becoming a trusted leader in providing Umrah packages and travel services. To streamline operations and enhance services, the study adopts the waterfall model for system development. The article presents the results and discussion, focusing on the system interface's design, illustrated by the main page. Black box testing validates the functionality of user and admin interfaces, ensuring that all proposed functions operate effectively. The testing criteria cover aspects such as menu display, login functionality, travel package registration, and administrative tasks, all validated. In conclusion, the study affirms the successful implementation of the computerized web-based system at El-Fajr Palembang, poised to enhance Umrah pilgrim registrations, activity schedules, and information dissemination. The system aligns with El-Fajr Palembang's vision to become a leading travel and tour company, demonstrating the potential of web technology in optimizing service delivery.